Gen-Y’s Aura Impact on HR New Model and Practices of Hospitality Sector - Jakaria Dasan; Jennifer Chan Kim Lian; Sharija Che Sha’ari (2016)
Gen-Y’s employees could elicit an aura that would support the development of a sustainable HR model and practices in hospitality sector, particularly in hotel industry. Subsequently, this could revive the glaring hospitality industry which initially being portrayed through hotel. Yet, a worrying perception was unveiled that Gen-Y was reluctant to engage in a face-to-face approach, which has long become the trademark in hospitality business. This tendency might pose a challenge to the development of the aforementioned HR model and practices. Data collected from the Gen-Y cohort, and the multi-generations workforce prevail the real traits, values and work attitudes of the Gen-Y. The information would improve further the human resource practices and management. The study employed a qualitative method by conducting interviews with the three levels of staffs in the participating hotels; namely, managerial level, supervisor level, and operational level. In total, 149 respondents were interviewed. Preliminary findings found that positive support from the Baby Boomer and Gen-X will bring out Gen-Y’s best aura that could position hotel industry into a driving seat of prosperous economy.